Respuesta :

DeanR

Part i


[tex] \dfrac{2a-7}{6y} = \dfrac{3b-5}{2c}[/tex]


[tex]y = \dfrac{ 2c(2a-7)}{6(3b-5)} = \dfrac{c(2a-7)}{9b-15} [/tex]


Substituting,

[tex]y = \dfrac{4(2(2)-7)}{9(3)-15} = \dfrac{ -12}{12} = -1[/tex]


Answer: -1


Part ii


I'm not sure that one's typed in correctly but I'll solve it as written.


[tex]3-34y + 2a = \dfrac{3b-5}{2c + 1}[/tex]


[tex]34y = 3+2a-\dfrac{3b-5}{2c + 1}[/tex]


[tex]y = \frac 1 {34}\left(3+2a-\dfrac{3b-5}{2c + 1} \right)[/tex]


We're not asked to simplify it so I wont. Substituting,


[tex]y = \frac 1 {34}\left(3+2(2)-\dfrac{3(3)-5}{2(4) + 1} \right) = \frac 1 {34}(7-4/9) = \dfrac{59}{306}[/tex]


Answer: 59/306